Persepsi dan Sikap Konselor terhadap E-konseling: Potensi Implementasi dalam Program Konseling Komprehensif - Atmarno, Tri Widati Setiya (Didaktika, 2021)
The purpose of this ex-post facto study is to analyze the Indonesia counselors’ perception, attitude, and potential about using Technology for counseling practice in senior high school. The subjects of this research were 50 school counselors in Surakarta, Indonesia. The questionnaire was developed and adapted based on literature review and experts’ opinion and sent to counselors electronically. Findings were analyzed by using descriptive statistics and ANCOVA to see the correlation between the perception and attitude on potential on applying technology in counseling. Counselors’ perception and attitudes toward using technology in counseling were also examined by content analysis. Results indicated that counselors have positive perceptions about e-counseling. From the investigation, the counselors’ perceptions were categorized as moderate. This study also found that the respondents were categorized as high in attitude toward e-counseling. From those aspects investigated, it indicated that counselor had the potential to implement e-counseling in the future. Then the attitude to adopt e-counseling is influenced by the counselor's perception. It can be potential to foster the effectiveness of counseling and further comprehensive counseling therapy since counselor perception can positively support the long-life and effective counseling process